CLINICAL SIGNIFICANCE OF ULTRASOUND DIAGNOSTICS IN INFLAMMATORY, PRECANCEROUS DISEASES AND BREAST CANCER - Arman Khozhayev; Erlan Tanzharykov; Gulmira Begalieva; Dinoram Ababakriyeva; Anar Kassimova; Moldir Satybaldy; Elnara Gunyasheva; Assel Kuralbek; Samal Moldazhanova (World Scientific Reports, 2025)
this scientific and analytical work presents the clinical aspects of ultrasound diagnostics of inflammatory, precancerous, and breast cancer, including rare pathologies. It provides a detailed and comprehensive overview of modern ultrasound diagnostic methods using various modes: B-mode alone, its combination with color Doppler and elastography, as well as their features and informative value in the differential and early diagnosis of pathological conditions of the mammary gland. Current proposals of ultrasound clinicians are provided in the following BI-RADS standard (6th edition). The possibilities of ultrasound correlation for nonspecific symptoms such as pain and discomfort in the mammary glands, known as mastalgia and mastodynia, are described. Clinical protocols for the diagnosis and treatment of various mammary gland pathologies are presented, and current international practices and trends regarding oncovigilance and early diagnosis of breast cancer, including screening, using ultrasound are described in detail